CD4 T Cells and Major Histocompatibility Complex Class II Expression Influence Worm Expulsion and Increased Intestinal Muscle Contraction during Trichinella spiralis Infection - Vallance, Bruce A. (American Society for Microbiology, 1999)
Expulsion of intestinal nematode parasites and the associated increased contraction by intestinal muscle are T cell dependent, since both are attenuated in athymic rodents. The CD4 T-cell subset has been strongly associated with worm expulsion; however, the relationship between these cells, antigen presentation, and worm expulsion is not definitive and the role of these factors in intestinal muscle hypercontractility has not been defined. We infected C57BL/6, athymic, CD4-deficient, CD8α-deficient, and major histocompatibility complex class II (MHC II)-deficient (C2d) mice with Trichinella spiralis larvae. We examined intestinal worm numbers, longitudinal muscle contraction, and MHC II expression. Numerous MHC II-positive cells were identified within the muscularis externa of infected but not uninfected C57BL/6 mice. C57BL/6 and CD8α-deficient mice developed large increases in muscle contraction, expelling the parasite by day 21. Athymic and C2d mice exhibited much smaller increases in muscle contraction and delayed parasite expulsion. CD4-deficient mice exhibited intermediate levels of muscle contraction and delayed parasite expulsion. To further examine the role of MHC II and CD4 T cells, we irradiated C2d mice and reconstituted them with C57BL/6 bone marrow alone or with C57BL/6 CD4 T cells. C57BL/6 bone marrow alone did not affect muscle function or worm expulsion in recipient C2d mice. Partial CD4 T-cell reconstitution was sufficient to restore increased muscle contraction but not worm expulsion. Thus, hematopoietic MHC II expression alone is insufficient for the development of muscle hypercontractility and worm expulsion, but the addition of even small numbers of CD4 T cells was sufficient to induce intestinal muscle pathophysiology.